Habitats and Characteristics of Sardina pilchardus, off the Moroccan Atlantic coast - Abdelaziz Mounir; Hassan Alahyane; Nor-eddine Chouikh; Nawal Hichami; Safaa Bendami (Annals of Marine Science - Peertechz Publications, 2022)
This paper is an overview of the main characteristics of Sardina on the Moroccan Atlantic coast. Sardine occupies an important place in the socio-economic context of Morocco and is the main species exploited on Moroccan coasts. It is the most important species in terms of catches and biomass. The small pelagic stocks in the area are exceptional wealth and as many opportunities in an international context, marked both by the scarcity of the resource and the need to make the sea c contribute more to food security and economic growth. The aim of this work is the study some features of S. pilchardus in the Moroccan waters.